Integration of Functional Linguistic Theory in Text-Based Indonesian Language Learning in Senior High School: A Literature Review - Budi, Imanuel Setyo; Suandi, I Nengah; Ida Bagus Putrayasa (Journal of Practice Learning and Educational Development, 2025)
This article is a literature review that discusses the integration of functional linguistic theory in text-based Indonesian language learning at the secondary school level. Functional linguistic theory, especially that developed by Halliday, emphasizes that language functions as a tool to construct meaning in a social context. In the context of learning, this approach is relevant to the Independent Curriculum which prioritizes text-based learning. This article analyzes various literature related to the application of functional linguistic theory in Indonesian language teaching, covering aspects of text structure, situational context, and the social function of language. The results of the review show that the integration of this theory can improve students' literacy competencies, deepen their understanding of text structure and function, and encourage more contextual and meaningful learning. This study recommends the development of more structured teaching tools and teacher training to support the implementation of functional linguistic theory in learning practices.